PENGARUH GREEN BRAND IMAGE DAN GREEN PERCEIVED VALUE TERHADAP GREEN TRUST DAN GREEN BRAND EQUITY - Mahendra, I Made Gilang; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
The purpose of this study to determine the effect of green brand image, green perceved value on green trust and the green brand equity of Ades bottled water products in Denpasar. The samples used were 100 people and collected through non-probability sampling method. Data were collected by distributing questionnaires and using Likert scale. The analysis technique used is PLS. The analysis showed green brand image influence positively and significantly to the green green trust and brand equity. Green perceived value affect positively and significantly to green and green brand equity trusts, and green trust influence positively and significantly to the green brand equity.